MODIFICATION OF THE ENGINE CONTROL UNIT AND ITS IMPACT ON FUEL CONSUMPTION AND VEHICLE PERFORMANCE - Sarkan, Branislav; Vrabel, Jan (Doprava a spoje, 2012)
The fuel consumption is influenced by several factors. Engine control unit is responsible for preparing the fuel mixture. On the basis of the measurements we analysed the effect of setting engine control unit on fuel consumption and vehicle performance. The tests were performed in laboratory conditions.